Fundamentals of wireless communication - Tse, David; Viswanath, Pramod (Cambridge University Press, 2005)
This textbook takes a unified view of the fundamentals of wireless communication and explains cutting-edge concepts in a simple and intuitive way. An abundant supply of exercises make it ideal for graduate courses in electrical and computer engineering and it will also be of great interest to practising engineers.